Grass evapotranspiration-induced suction in slope: case study. Issue 3 (15th July 2014) - Leung, Anthony Kwan
Abstract : Grass evapotranspiration (ET) has been recognised to potentially affect shallow slope stability due to additional soil suction induced by root–water uptake. Some limited field studies showed higher suction induced in vegetated soil than that in bare soil, but some reported the opposite. In order to improve the understanding of the hydrological role of grass ET, this study explores suction responses of grassed slopes based on the current knowledge of soil–water–root interaction on root–water uptake in unsaturated soil. Three case histories, which included measurements of suction in both bare and grassed slopes, are selected for new interpretation. It is revealed that during drying, ET-induced suction in grassed slope was not necessarily higher than that by evaporation in bare slope. When grass ET took place in relatively wet soil that has insufficient soil aeration (i.e. suction lower than that corresponding to anaerobiosis point; 5–12 kPa for sandy soil), induced suction in grassed slope could be 20% lower. During rainfall, the presence of grass appears to help in retaining higher suction in slope composed of silty clay, as compared with bare slope. On the contrary, for sandy soil, no discernible difference of suction retained between grassed and bare slopes is observed.